IMPLEMENTASI PEMBELAJARAN JARAK JAUH (PJJ) PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAMDI SEKOLAH LUAR BIASA (SLB) NEGERI MUARA ENIM - Widya Wulandari; Abu Mansur; Mukti Ali (Jurnal PAI Raden Fatah, 2022)
Distance learning that is being carried out in special schools, especially for children with special needs for mental retardation who can still be given education in schools and Islamic Religious Education lessons are expected to be able to encourage students to grow noble characters and personalities. The purpose of this study was to find out how the implementation of distance learning in Islamic Religious Education subjects at SLB Negeri Muara Enim, especially for children with special needs for mental retardation. This research is a type of field qualitative research (field research) with a qualitative descriptive approach to fully understand the phenomenon of the implementation of distance learning in Islamic Religious Education subjects for mentally retarded children. Data collection techniques in this study were obtained by means of observation, interviews, and documentation, in which the informants consisted of principals, PAI teachers, and parents of mentally retarded students at the Muara Enim State Special School. Furthermore, the method used in this study is a descriptive method based on the results of interviews and observations. The data validity technique was carried out by triangulation while the data analysis technique was by means of data reduction, data presentation, and conclusions.